Fenomena Childfree Berdasarkan Perspektif Hukum Islam Progresif, Pancasila dan Hak Asasi Manusia (HAM) - Nasution, Chairul Majid; Saputra, Gusti Rian (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The childfree phenomenon in normative legal studies is considered an aberration. Islamic law scholars refer to various considerations, ranging from being contrary to nature, not being in accordance with national culture and threatening human civilization. However, in certain cases childfree becomes an alternative because there is an element of unintentional doing it. Call it for health, psychological and other reasons. Strict restrictions on childfree practices when it is done intentionally and views having children as a burden. This research uses qualitative methods and is a library research type. Researchers use a normative legal approach in analyzing data. The analysis technique used is descriptive analytic. Data is taken from various literature such as books, journals, scientific works, official websites and related sources according to the research theme. The results of the research show that according to the progressive Islamic and Pancasila views, childfree is possible for health and psychological reasons. Apart from that, childfree is a person's private choice that cannot be interfered with by other people.